PENGENDALIAN HAMA WALANG SANGIT (Leptocorisa acuta Thunb.) DENGAN MENGGUNAKAN PERANGKAP BANGKAI IKAN DAN KEONG PADA TANAMAN PADI - Ruth Kristivoni Buida; Daisy Kandowangko; Vivi B. Montong (Universitas Sam Ratulangi, 2022)
BSTRACT Walang sangit is an important pest in rice plants. Because of the attack of walang sangit on rice crops in the flowering phase, farmers suffer losses because the grain of rice does not produce. The attack of pests that are high enough to cause rice crops to fail to harvest or reduce the quality of grain and the quantity of production. To prevent the attack of walang sangit on rice plants, it is necessary to control environmentally friendly walang sangit pests to suppress the impact of pesticide use by finding alternative substitutes, namely with carcass smell extracts, in this case using fish and conch carcasses. The purpose of this study is to find out the extent to which fish and conch carcasse traps can be used for pest control in rice plants located in Kiniar Village of Tondano Subdistrict during Minahasa Regency and implementation time from March to July 2021. This study used 2 treatments, namely fish carcass traps and conch carcasses, each treatment using a carcass mass weighing 150 grams, with 10 repeats. The results showed that both of these treatments can give good results where the pest walang sangit is attracted to both traps although in the treatment of fish carcass traps are able to attract more pests walang sangit with a value of 64.9 tails, and in the trap of conch carcass 38.7 tails. The results of the test analysis of the average difference between two free samples proved that the value of thitung > ttabel, which is 4.38 > 2,101, thus the hypothesis is proved to be H0 in rejected and H1 to be accepted. Keyword : Walang Sangit, carcass smelling accretion, fish and conch carcass traps